Shell and Body of Cat Character Robot for Early Intervention to Treat Children with Autism Spectrum Disorders - Jung, Jin Soun; Lee, Bo Lee; Lee, Jin Gyu (International Journal of Advanced Science and Technology, 2019)
Despite consistent increase in the number of children with Autism Spectrum disorders(ASD), supply of professional facility or experts to treat the children with such condition are in great shortage. The goal is to develop functional material that can be used as shell for the robot not only to protect the robot user from harmful environment such as dust-mite, germs and etc., but also to support the emotional treatment of the robot user with its aromaticity and body action using gesture. Using the faux fur developed as part of this study, the shell of cat character robot was completed based on the drawn pattern. In the process of treating children with ASD, the keys are to promote interaction, to encourage children to exercise appropriate social skills and to enhance ability to adapt. This study aims to develop a robot that is tailored to children with ASD who experience difficulties in interaction and in forming emotional bonding with others, so that the robot can be effectively leveraged together with various treatment approaches currently employed. As part of such effort, Jasmin tea extract dyed faux fur which illustrates outstanding house dust mite repelling, anti-microbial, and aromatic functionality was developed and used as shell of the robot, so that not only emotional treatment but also the hygiene of the children can be considered at the same time. Furthermore, considering that children with ASD shows tendency of bringing toys to their mouths and that the toys needs to be washed frequently, the shell of the robot should be easily removed and applied, which will contribute to higher usability satisfaction level of the caregivers. In this paper, the field experiment was carried out to show the efficiency of the design and found the validness of this concept. This robot developed with the goal of early intervention for children with ASD is expected to reap synergy together with other treatment approaches.Keywords: Autism Spectrum disorders(ASD), Emotional treatment, Shell of cat character robot, Jasmin Tea, Dye